普通话与新加坡华语量词 “条、根、支、道”之比较研究 = Comparison of Mainland and Singapore Mandarin Chinese on the usage of classifiers ‘Tiao’, ‘Gen’, ‘Zhi’, ‘Dao’ - 覃玮婷 Sam, Wei Ting (2017)
量词是汉语的⼀⼤特点。量词“条”、“根”、“⽀”、“道” 都可⽤于修饰具有显著的“长条形”或“线状”的外形特征的事物名词，因⽽经常被列为⼀组近义量词相提并论。然⽽现有关于这组量词的研究的⽂献⼤都基于研究者的语感或有限的语料。另外，许多研究都是以普通话为对象，针对为汉语变体之⼀的新加坡华语的量词研究少之又少。本⽂以语料库为语料来源，利⽤统计的⽅法分别探究普通话与新加坡华语中量词“条”、“根”、“⽀”、“道”之间的差异，再对⽐分析这⼏个量词在新加坡华语与普通话的差异。本⽂发现，⽆论是普通话还是新加坡华语，四个量词之间都有很⼤的区别；反之，普通话与新加坡华语在四个量词的使⽤上只有⾮常微⼩的区别。本研究的所得结果既能更客观地说明量词“条”、“根”、“⽀”、“道”的现时⽤法及其之间的差异，也能为新加坡华语的量词⽤法提供参考。Classifier is one of the special characteristics of the Chinese language. The four classifiers 条 tiao, 根 gen, 支 zhi, and 道 dao can often be used to modify nouns that denote long or liner entities and are thus considered a set of synonymous classifiers. The current studies on this set of classifiers, however, are mostly based on researchers’ language intuition or limited language data. Furthermore, despite the larger number of studies on these classifiers in Mainland Mandarin Chinese (MMC), few have worked on Singapore Mandarin Chinese (SMC), a variety of Modern Standard Mandarin Chinese. Taking a corpus-based and statistical approach, this study aims to investigate how the four classifiers can be distinguished from each other in MMC and SMC respectively, and how each classifier differ in the two varieties of Chinese. This study finds that the four classifiers can be distinguished from each other in both MMC and SMC, but each classifier does not show significant variation between MMC and SMC. The findings of this study can serve as importance references for studies on classifiers and language variation.